Cartographic model of the spatial change of soil by sub-basins in Texcoco, Estado de Mexico: 1977-2000 - Escalona Maurice, Miguel J.; Jiménez Moreno, María Josefa; Sancho Comíns, José (Revista Mexicana de Ciencias Agrícolas, 2017)
In this research, Landsat satellite images of the 1977 year MSS, 1989 TM and 2000 ETM were used to analyze the morphological and functional status of the sub-basins landscape of the Texcoco municipality. In the municipality there are seven sub-basins and two divisions of water between the Mexico Basin and the section corresponding to the Puebla-Tlaxcala Basin. The analysis indicates that six sub-basins showed drastic changes in relation to the vegetation type, grassland, scrubland and forest, and in the agricultural surface under irrigation and rainfed. The Manzano River subbasin in the study period maintains a relative equilibrium because it does not show changes in the natural vegetation surfaces and productive areas. Based on data El Tejocote-Santa Mónica subbasin is considered as an area with no alteration in its land use.